On the Relevance of Open Market Operations - Andreas Schabert (Hamburg Institute of International Economics (HWWA), 2004)
This paper reexamines the role of open market operations for short-run effects of monetary policy. Money demand is induced by a cash constraint, while the central bank supplies money exclusively in exchange for securities, discounted with a short-run nominal interest rate. We consider a legal restriction for open market operations by which only government bonds are eligible, whereas private debt is not accepted as collateral for money. Supply of eligible securities is bounded by assuming fiscal policy to ensure government solvency. The model provides an endogenous liquidity premium on noneligible assets and liquidity effects of money supply shocks regardless whether prices are flexible or set in a staggered way. Nominal interest rate policy is always associated with a uniquely determined price level and rational expectations equilibrium. It is further shown that an intuitive equivalence principle between money supply and interest rates arises in this case.
Keywords: E52; E32; 330; Inside Money; Liquidity Puzzle; Risk-free Rate Puzzle; Ricardian Fiscal Policy; Price Level and Equilibrium Determinacy; Offenmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Konjunkturtheorie; Geldtheorie; Theorie